Role of Community Health Workers in Delivering Mental Health Services in Lower-Middle-income Countries: Perspectives from the Maanasi Project - Samrat Gali; Swati Chandramouli; Sachin Nagendrappa; Suhas Chandran; B. Ramakrishna Goud; Johnson-Pradeep Ruben; Geetha Jayaram (Indian Journal of Social Psychiatry)
Lay members of the community who receive training in providing basic health care to the community, called community health workers (CHWs), have been the focus of much research in the various fields of health. In recent years, the use of CHWs in catering to the mental health needs of the community has received a lot of attention. The needs are felt more in low- and middle-income countries where resources are minimum, and professional mental health services are either scarce or difficult to access. Research has shown that task-shifting from professional to nonprofessional health-care personnel has proven effective in delivering health care. The utility of CHW has proven useful in depression, perinatal mental health, suicide prevention, and schizophrenia. We present a model from the Maanasi Mental Health Project, in which CHWs from a rural setting are trained to screen, educate, and deliver therapies in mental health in the villages of Mugalur in Karnataka, South India. The utilization of a special software called e-Maanasi for use by the CHWs in the Maanasi Mental Health Project is also described. To conclude, CHWs can be utilized as a vital resource in delivering mental health in resource-poor settings. Utilization of technology by the CHWs is feasible, although ongoing training and supervision are essential.